Odpowiedź :
Odpowiedź:
1) 2x+9=1
2x=1-9
2x=-8
x=-4
2)2x+7=x-1
2x-x=-1-7
x=-8
3)5(x-7)+2=-28
5x-35+2=-28
5x=-28=35-2
5x=5
x=1
4)4(3-x)+9=7(2+x)+29
12-4x+9=14+7x+29
21-14-29=7x+4x
-22=11x
-2=x
5)9=5x+6-5(x-0,6)
9=5x+6-5x+3
9-6-3=5x-5x
0=0
Szczegółowe wyjaśnienie:
Liczę na najjj
2x + 9 = 1
2x = 1 - 9
2x = -8 |:2
x = -4
2x + 7 = x - 1
2x - x = -1 - 7
x = -8
5(x-7) + 2 = -28
5x - 35 + 2 = -28
5x - 35 = -28-2
5x - 35 = -30
5x = -30 + 35
5x = 5 |:5
x = 1
4(3-x) + 9 = 7(2+x) + 29
12 - 4x + 9 = 14 + 7x + 29
-11x = 14 + 29 - 9 - 12
-11x = 22 |: -11
x = -2
9 = 5x + 6 -5(x-0,6)
9 = 5x + 6 -5x + 3
9 = 9